Case of Severe Treatment-Resistant Cryptogenic Organizing Pneumonia - Grigoravičius, Domas; Žurauskas, Edvardas; Gruslys, Vygantas; Zablockis, Rolandas; Danila, Edvardas (Acta medica Lituanica, 2021)
Cryptogenic organizing pneumonia is a rare interstitial lung disease with different onset of symptoms, which responds rapidly to glucocorticoid treatment. We present a case of cryptogenic organizing pneumonia which manifested as a progressive 3-year dyspnea that ultimately has led to acute respiratory failure. Moreover, treatment with prednisone for this patient exhibited slow onset of the effect.